State Authority for Management of Zakat, Infaq, and Sadaqah as Locally-Generated Revenue: A Case Study at Baitul Mal in Aceh - Mahdi Syahbandir; Wais Alqarni; Dahlawi MAZ; Abdul Hakim; Bunyamin Muhiddin (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Aceh is a region with an autonomy in implementing Islamic law (sharia) and Baitul Mal is one of the institutions formed by the local government to support it. This article aims to discuss the authority of the state in managing zakat, infaq, and sadaqah (ZIS), and describe the authority of the Baitul Mal in managing ZIS as locally-generated revenue (PAD) in Aceh. The study used a case study approach by using the theory of authority as an analytical tool. Data collection techniques were carried out through interviews and document studies. The informants interviewed were the staff of the Baitul Mal and the staff management of the Ulema Consultative Council (MPU) in Pidie Regency and Sabang City. It found that the state, in this case, Baitul Mal, has the authority to manage ZIS which can be treated as PAD. This practice has contributed to poverty alleviation, scholarships, business capital, and community economic empowerment in Aceh. To facilitate the management of zakat funds, lex specialis can be applied as a position of Islamic law in the national legal framework.